2016
DOI: 10.15407/ukrbotj73.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Stages in the evolution of the genus Stipa and formation of steppes

Abstract: Stages in the evolution of the genus Stipa and formation of steppes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
3
0
3
Order By: Relevance
“…Forest and related biotopes present within the Moshnohirsky Ridge are shown in Table 1. Previous studies have confirmed the botanical uniqueness and conservation value of the Moshnogirya area (Udra, 1983;Didukh et al, 1987;Gaiova, 2008). Within the territory, a number of objects of the nature reserve fund have been established, including two local landscape reserves ("Moshnohirsky" and "Moshnivsky"), a nationally significant natural monument "Moshenska Dibrova", three botanical monuments ("Velvet Amur Plantation", "Group of Mature Firs", "Alder Tree with Oak"), a local zoological reserve "Moshnivsky Conservation Zone", and two hydrological monuments ("Cascade of Forest Lakes", "Subterranean Spring").…”
Section: Resultsmentioning
confidence: 69%
“…Forest and related biotopes present within the Moshnohirsky Ridge are shown in Table 1. Previous studies have confirmed the botanical uniqueness and conservation value of the Moshnogirya area (Udra, 1983;Didukh et al, 1987;Gaiova, 2008). Within the territory, a number of objects of the nature reserve fund have been established, including two local landscape reserves ("Moshnohirsky" and "Moshnivsky"), a nationally significant natural monument "Moshenska Dibrova", three botanical monuments ("Velvet Amur Plantation", "Group of Mature Firs", "Alder Tree with Oak"), a local zoological reserve "Moshnivsky Conservation Zone", and two hydrological monuments ("Cascade of Forest Lakes", "Subterranean Spring").…”
Section: Resultsmentioning
confidence: 69%
“…8. Distribution of coprinoid taxa (marked by dark) within the family Agaricaceae (Johnson, 1999, with some changes від кри ті сухі трав'янисті це но зи (са ван но го та сте по во го типу), що су про во джу ва ло ся збіль шен ням ви до во го різ но ма ніт тя ве ли ких тра во їд них ссав ців (Janis et al, 2000;Didukh et al, 2016). Ос тан нє, без у мов но, спри яло на ко пи чен ню ве ли кої кіль кості субстра тів, при дат них для роз ви тку гри бівко про тро фів, і мог ло пос прия ти їхньо му ін тен сив но му ви до ут во рен ню.…”
Section: вступunclassified
“…8. Distribution of coprinoid taxa (marked by dark) within the family Agaricaceae (Johnson, 1999, with some changes від кри ті сухі трав'янисті це но зи (са ван но го та степо во го типу), що су про во джу ва ло ся збіль шен ням ви до во го різ но ма ніт тя ве ли ких тра во їд них ссав ців (Janis et al, 2000;Didukh et al, 2016). Ос тан нє, безу мов но, спри яло на ко пи чен ню ве ли кої кіль кості субстра тів, при дат них для роз ви тку гри бів-ко протро фів, і мог ло пос прия ти їхньо му ін тен сив но му ви до ут во рен ню.…”
Section: вступunclassified